Super-enhancers complexes zoom in transcription in cancer - MengTing Wang; QingYang Chen; ShuJie Wang; Han Xie; Jun Liu; RuiXiang Huang; YuFei Xiang; YanYi Jiang; DaSheng Tian; ErBao Bian (Journal of Experimental & Clinical Cancer Research, 2023)
Abstract Super-enhancers (SEs) consist of multiple typical enhancers enriched at high density with transcription factors, histone-modifying enzymes and cofactors. Oncogenic SEs promote tumorigenesis and malignancy by altering protein-coding gene expression and noncoding regulatory element function. Therefore, they play central roles in the treatment of cancer. Here, we review the structural characteristics, organization, identification, and functions of SEs and the underlying molecular mechanism by which SEs drive oncogenic transcription in tumor cells. We then summarize abnormal SE complexes, SE-driven coding genes, and noncoding RNAs involved in tumor development. In summary, we believe that SEs show great potential as biomarkers and therapeutic targets.